Комп'ютеризований діагностичний комплекс для випробувань електричних машин на надійність - Сьомка, Олександр Олександрович; Прус, В'ячеслав В'ячеславович (НТУ "ХПІ", 2015)
Розроблено структуру діагностичного комплексу для випробувань електричних машин на надійність, що забезпечує необхідні режими роботи при варіюванні температурних і вібраційних факторів. Запропонований комплекс є уніфікованим та дозволяє враховувати дійсний стан досліджуваної машини, а режими випробувань не порушують фізику процесів старіння і зношування конструктивних вузлів та матеріалів.

Purpose. To develop a diagnostic complex meeting the criteria and requirements for carrying out accelerated reliability test and realizing the basic modes of electric machines operation and performance of the posed problems necessary in the process of such test. Methodology. To determine and forecast the indices of electric machines reliability in accordance with the statistic data of repair plants we have conditionally divided them into structural parts that are most likely to fail. We have preliminarily assessed the state of each of these parts, which includes revelation of faults and deviations of technical and geometric parameters. We have determined the analyzed electric machine controlled parameters used for assessment of quantitative characteristics of reliability of these parts and electric machines on the whole. Results. As a result of the research, we have substantiated the structure of a computerized complex for electric machines reliability test. It allows us to change thermal and vibration actions without violation of the physics of the processes of aging and wearing of the basic structural parts and elements material.
A computerized diagnostic complex for reliability testing of electric machines
Keywords: електричні машини; надійність; вібраційні фактори; electric machine; reliability; vibration parameters